Effect of excessive and minimal soil moisture stress on agronomic performance of bush and climbing bean (Phaseolus vulgaris L.) - Ntukamazina, Nepomuscene; Onwonga, Richard N.; Sommer, Rolf; Mukankusi, Clare Mugisha; Mburu, John; Rubyogo, Jean-Claude (Informa UK Limited, 2017)
Water stress is a major crop production constraint for common bean (Phaseolus vulgaris L). The response of bush and climbing bean to excessive and minimal soil moisture at various plant growth stages was investigated under greenhouse for two growing periods; September-February 2016 and March-July 2016. The control consisted in watering with recommended rates for each plant growth stage. Two bean genotypes RWR2245 (bush bean) and MAC44 (climbing bean) were used for this study. The minimal soil moisture (drought stress) treatment consisted of withholding water supply, from the on-set of emergence, vegetative, flowering, pod setting and seed filling growth stages, up to the wilting point of plants. The excessive soil moisture (waterlogging stress) was achieved by saturating the soil on a daily basis for five successive days, starting from the on-set of the aforementioned plant growth stages. For each genotype, these treatments were replicated four times and arranged in a Completely Randomized Design. Drought stress accelerated the number of days to maturity whilst waterlogging stress tended to increase the number of days to maturity. Both stresses reduced the agronomic performance of both genotypes. However, pod setting and flowering were the most sensitive stages to drought stress and waterlogging stress, respectively.